From proliferative to neurological role of an hsp70 stress chaperone, mortalin - Deocaris, Custer C. (Animo Repository, 2008)
Although the brain makes up approximately 2% of a person's body weight, it consumes more than 15% of total cardiac output and has a per capita caloric requirement of 10 times more than the rest of the body. Such continuous metabolic demand that supports the generation of action potentials in neuronal cells relies on the mitochondria, the main organelle for power generation. The phenomenon of mitochondrial biogenesis, although has long been a neglected theme in neurobiology, can be regarded as critical to brain physiology. The present review emphasizes the role of a key molecular player of mitochondrial biogenesis, the mortalin/mthsp70. Brain mortalin is discussed in relation to its aptitude to impact on mitochondrial function and homeostasis, to its interfacing energy metabolic functions with synaptic plasticity, and to its modulation of brain aging via the cellular senescence pathways. Recently, this chaperone has been implicated in Alzheimer's (AD) and Parkinson's (PD) diseases, with proteomic studies consistently identifying oxidatively-damaged mortalin as potential biomarker. Hence, it is possible that mitochondrial dysfunction coincides with the collapse in the mitochondrial chaperone network that aim not only to import, sort and maintain integrity of protein components within the mitochondria, but also to act as buffer to the molecular heterogeneity of damaged and aging mitochondrial proteins within a ROS-rich microenvironment. Inversely, it may also seem that vulnerability to mitochondrial dysfunction could be precipitated by malevolent (anti-chaperone) gain-of-function of a 'sick mortalin'.